Acute inflammatory demyelinating polyradiculoneuropathy presenting as complete heart block and Stoke-Adams attacks. Issue 760 (February 1989) - Wani, B. A.; Misra, M.; Shah, M.; Mufti, S.
Abstract : A patient with acute inflammatory demyelinating polyradiculoneuropathy (AIDP, Guillain-Barré syndrome) whose presenting complaints were related to autonomic dysfunction in the form of parasympathetic and sympathetic overactivity is reported. Parasympathetic overactivity was severe enough to cause complete atrioventricular block (atropine-responsive) and Stoke-Adams attacks, for which a demand pacemaker was required. Limb weakness was apparent 48 hours later. To our knowledge no such presentation of AIDP has been previously recorded.